2018
DOI: 10.1042/bsr20180036
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 in extracellular vesicles contributes to the growth of fertilized eggs and embryo development in mice

Abstract: Human preimplantation embryo development is susceptible to high rates of early embryo wastage. We determined the miR-21 expression of extracellular vesicles (EVs) in fertilized eggs and embryos of varying stages and their response to miR-21 microinjection. Sexually mature female and male mice were mated. Next, the expression and immunohistochemistry intensity of surface markers (CD9 and CD63) of EVs were detected in pregnant and non-pregnant mice. Exosomes were co-cultured with embryos for detection of blastoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…In our ongoing study, we found that differentially expressed miRNAs in EVs from outgrowth embryos, comparing those from blastocysts—including miR‐30d, let‐7b, and miR‐429—have functions on various biological processes such as cell communication, cell growth, and proliferation, death, system, and embryo development. Increased expression of miR‐21 was detected in EVs from uterine luminal fluid or pregnant mice have roles in regulating of embryonic development and apoptotic genes expressions such as Bcl2 and Bax identified by loss of function assay (Lv et al, ). Recently, roles of let‐7 family and miR‐429 have been revealed in cell proliferation, apoptosis, implantation, and development process (Al‐Nakhle et al, ; Johnson et al, ; Schickel, Park, Murmann, & Peter, ; Wang et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our ongoing study, we found that differentially expressed miRNAs in EVs from outgrowth embryos, comparing those from blastocysts—including miR‐30d, let‐7b, and miR‐429—have functions on various biological processes such as cell communication, cell growth, and proliferation, death, system, and embryo development. Increased expression of miR‐21 was detected in EVs from uterine luminal fluid or pregnant mice have roles in regulating of embryonic development and apoptotic genes expressions such as Bcl2 and Bax identified by loss of function assay (Lv et al, ). Recently, roles of let‐7 family and miR‐429 have been revealed in cell proliferation, apoptosis, implantation, and development process (Al‐Nakhle et al, ; Johnson et al, ; Schickel, Park, Murmann, & Peter, ; Wang et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of miR-21 was detected in EVs from uterine luminal fluid or pregnant mice have roles in regulating of embryonic development and apoptotic genes expressions such as Bcl2 and Bax identified by loss of function assay(Lv et al, 2018). Recently, roles of let-7 family and miR-429 have been revealed in cell proliferation, apoptosis, implantation, and development process(Al-Nakhle et al, 2010;Johnson et al, 2005;Schickel, Park, Murmann, & Peter, 2010;Wang et al, 2013;Zhang et al, 2015).…”
mentioning
confidence: 99%
“…Overall, the results revealed a network of genes and their regulatory miRNAs that suggested a mode of action of transferred oEV cargo inducing changes in embryonic gene expression which lead to a decrease in apoptosis of embryonic cells and improved embryo viability. For a variety of the identified miRNAs, a positive effect on embryonic development has been shown, for example miR-23a-3p with increased expression in outgrowth embryos in the mouse [75], and miR-21-5p with positive effects on the development of murine embryos [76]. In-vitro-produced bovine embryos cultured in the presence or absence of oEVs for 8 days were used for transcriptomic analysis by RNA sequencing in this study.…”
Section: Unveiling the Potential Of Oev Rna Components To Regulate Emmentioning
confidence: 99%
“…Among these miRNAs, ssc-miR-21-5p was the most abundant in all libraries. MiR-21 (miR-21-5p) in extracellular vesicles is conducive to embryo development and prevention of high embryo death rate [32]. MiR-21-5p was also found in ovine mammary gland [33] and milk [34] during early pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The microvesicle-like particles are present in saliva, plasma, milk, urine, semen, uterine luminal fluid and other biological fluids [11][12][13][14]. Moreover, these microvesicles have been isolated and characterized from the ULF in human [15], mice [16], cattle [17,18], and sheep [19]. However, porcine ULF exosomes have not been isolated and identified so far.…”
mentioning
confidence: 99%